Limites e possibilidades da participação e representatividade da classe trabalhadora nos conselhos estaduais de educação em tempos de epidemia - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This thesis results from documental bibliographic research that, in light of praxis philosophy, has as object the participation and representativeness of the working class in the State Councils of Education. The research problem consists in answering: what are the limits and possibilities of the working class in the SCEs? As a general objective, the thesis proposes to comprehend these limits and possibilities. We delimited the acts of SCEs about the Covid-19 pandemic as selection criteria for the documents. The first chapter presents the approximation of the research object. We broach the context of the Covid-19 pandemic for the working class. We discuss the importance of class participation and representativeness in decision spaces, as well as the current complexity and heterogeneity of the working class. As an expression of class conflict, we expound on conservatism, tracing a situation analysis of the 2013-2020 interregnum. At the end of the section, we thread considerations about the limits of bourgeois democracy and the possibilities of the working class in these boundaries. Authors such as Bordenave (1986), Gramsci (1999, 2002, 2017), Antunes and Alvez (2004), Chauí (2013; 2016), Escorsim Netto (2011), Iasi (2015), Miguel (2018) and Almeida (2019) have served as our foundation. In chapter 2, we present the Council as form of organization and denounce threats these instances have been suffering in Brazil today. We highlight some Councils of revolutionary character in history, expound on Councils in Brazil and broach the development of Councils of Education from the Brazilian legislation. Finally, we present the State Councils of Education based on literature review. This section counted on theoretical contributions from authors such as Valle (1991), Garcia (2004), Garrosino (2007), Pelisser (2008), Hoff (2008), Aquino (2009), Gonh (2006; 2011), Raggio (2014), Viana (2011), Gramsci (2004), etc. Chapter 3 traces the landscape of SCEs in Brazil. Based on legal and normative documents, we describe aspects about the nature and composition of the SCEs of each state, problematizing aspects such as the amount of counselors, the influence of political society, the diversity in their composition and the institutions that represent workers. In the last chapter, we keep ourselves to the analysis of the declarations of contrary votes in the SCEs’ acts about special regimens during the pandemic. Backed by Semeraro (1999) and Acanda (2006), we discourse about the civil society, political society and hegemony. As a result, the thesis defended here is that the SCEs present various limits to the participation and representativeness of the working class, among them: the exacerbated influence of each state’s Executive Power; few seats for class institutions, absence of broader social participation and lack of clarity in the choice of counselors; excess of bureaucratic functions etc. As possibilities, we highlight that the SCEs are spaces of collective deliberation, which have the potential to harbor greater participation of the working class and to contest the acts of the Executive Power, can express class values and positions by way of declarations of contrary votes, and have reach over an entire education system.
Keywords: Conselhos Estaduais de Educação; Classe trabalhadora; Participação; Representatividade; Covid-19; State Councils of Education; Working clas; Participation; Representativeness; Covid 19; CNPQ::CIENCIAS HUMANAS::EDUCACAO